The Role of Fintech in Transforming Financial Services for Indian Start-Ups - Kumar , Dr. Gaurav; Raju , N S V N; Lakshmi , V.Gowri; vemuri , Suneetha; Rao , Jagdish Mohan; Chestor , Robert Edwin (International Journal of Accounting and Economics Studies, 2025)
This study examines the transformative impact of fintech on the financial services landscape for Indian start-ups, highlighting the role of digital innovation in redefining traditional financial models. By evaluating how fintech enhances financial inclusion and provides start-ups with accessible, efficient, and cost-effective solutions, the research sheds light on the unique challenges faced by start-ups, including high collateral requirements and stringent credit assessments. Utilizing a mixed-methods approach, the study combines quantitative analysis through a structured Likert scale questionnaire administered to start-up founders, employees, and financial professionals, with qualitative insights from a comprehensive literature review. The findings reveal significant benefits of fintech adoption, such as improved accessibility and reduced operational costs, particularly among younger, educated professionals in tech-centric industries. However, the study also highlights the trade-offs associated with fintech integration, including cybersecurity and regulatory risks. These insights underscore the need for targeted educational initiatives, robust regulatory frameworks, and enhanced trust-building measures to support the sustainable growth of fintech in the Indian start-up ecosystem.